A captação do som do violino: aspectos acústicos e estéticos - Leonardo Oliveira da Cunha (2006)
This paper deals with an investigation about the use and level of knowledge about microphones, pickups and electric violins. Several individuals were interviewed and, based on the results, we could notice a lack of knowledge on using the equipments and other indispensable elements to the violin pickup process. Aiming to broaden the knowledge of musicians and technicians, the text deals with issues that help solving deficiencies found in the interviews. The acquired information were crossed in order to supply subsidies on choosing and using equipments, and furthermore, possible corrections for a better violin pickup.